Recent Developments in Airbags - Koçak, Aytaç; Topçuoğlu, Melike; Aktaş, Ekin Özgür (The Bulletin of Legal Medicine, 2010)
The vehicles on the traffic are increasing in number everyday in our country and that’s why the traffic accidents are also increasing. There are two types of safety systems in cars. The Active Safety Systems on automobiles aim to prevent the accident before it happens (ABS, active suspension etc.) and the Passive Safety Systems aim to prevent the occupants during the accident (safety belts, airbags etc.) In 1967 air bags had been began to be put in cars by a German automobile company first as the passive safety system and in 1980’s they had become commonly used by drivers and after 1988 both by drivers and front seat passengers. Together with these developments it was seen that the airbags were saving lives together with the injuries they cause so in 1980’s new second generation depowered airbags were developed to prevent airbag caused injuries. And today new studies are in progress to develop the new generation airbags working with sensors that sense the position and weight of the passenger and also the severity and force of the crash to deploy at the most suitable pressure and at the most suitable time during the accident. Together with these new developments in motorcycle airbags and wearable airbags are done. Key words: Traffic accidents, passive safety systems, airbags, airbag injuries